Implementing of RCPs scenarios to estimate the population density of parlatoria date scale insect, Parlatoria blanchardii (Targioni-Tozzetti) (Hemiptera: Diaspididae) infesting date palm trees in Luxor Governorate, Egypt - Bakry, M. M.S.; Abdrabbo, M. A.A.; Mohamed, G. H. (Journal of Phytopathology and Disease Management, 2015)
The present work was carried out to study the effect of some climatic factors on the population density of the white date palm scale insect, Parlatoria blanchardii on date palm trees during three time series (2011-2040, 2041-2070 and 2071-2100) under four Representative Concentration Pathway (RCP) scenarios (2.6, 4.5, 6.0 and 8.5) as compared with the current population of the pest (average of population density from 2009 to 2013 years) at Esna district, Luxor Governorate, Egypt. Results showed that monthly observations of total population of P. blanchardii had three to four peaks of seasonal activity per year. The mean minimum temperature was the most effective variable in population changes by 18.9, 20.9 and 19.9% for nymphs, adult females and total population of P. blanchardii during the base year data, respectively. The obtained results revealed the all expected values for number of nymphs, adult females and total population of insect during the all different time series under all different RCPs scenarios were smaller in comparison to the current population of insect. Expected total population of insect will be smaller at time series of (2071-2100) as compared with the two time series of (2041-2070) and (2011-2040) under the scenarios of (RCP 4.5, RCP 6 and RCP 8.5). Also, the time series of (2071-2100) exhibited the highest percentage of decreasing of the number of nymphs, adult females and total population with an average of (25.84, 23.76 and 24.91%) as compared to the time series of 2040-2071 (24.68, 22.44 and 23.68%) and the time series of 2011-2040 (10.43, 10.17 and 10.31%), respectively. Furthermore, the RCP 8.5 scenario exhibit the highest population density of nymphs, adult females and total population P. blanchardii and the lowest decreasing percentage of population density of P. blanchardii as compared with the different RCPs during all different time series.Â